1996
DOI: 10.1177/106002809603001201
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Scale to Measure Directive Guidance by Pharmacists

Abstract: The PPDG is short and easy to administer, and showed validity and reliability. The PPDG scale should be useful in developing a better understanding of the process by which pharmacists influence healthcare outcomes, assessing variations in pharmaceutical care, and as a tool in identifying means of overcoming barriers to higher levels of pharmaceutical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 0 publications
3
16
1
Order By: Relevance
“…The two factors named "Instruction" and "Feedback and Goal Setting" tap important socially supportive behaviors provided by pharmacists as key aspects in the pharmaceutical care process (Kong & Wertheimer, 1994;Gupchup, et al, 1996). Results are similar to a study conducted in Australia which found that a modified version of the PPDG yielded two factors with similar content (Chapman, 2005).…”
Section: Factor Analysessupporting
confidence: 80%
See 2 more Smart Citations
“…The two factors named "Instruction" and "Feedback and Goal Setting" tap important socially supportive behaviors provided by pharmacists as key aspects in the pharmaceutical care process (Kong & Wertheimer, 1994;Gupchup, et al, 1996). Results are similar to a study conducted in Australia which found that a modified version of the PPDG yielded two factors with similar content (Chapman, 2005).…”
Section: Factor Analysessupporting
confidence: 80%
“…These values are higher than previously reported values (Gupchup, et al, 1996;Sen & Thomas, 2000;Singhal, et al, 2002), and indicate good internal consistency (Nunnally & Bernstein, 1994). McDonald's omega for the entire scale was .97.…”
Section: Internal Consistency Reliabilitysupporting
confidence: 42%
See 1 more Smart Citation
“…Some pharmacies continue to focus almost exclusively on dispensing functions, whereas others offer a wide variety of disease management and medication therapy management (MTM) services. Although a number of measures have been developed to assess patient perceptions of the quality of outpatient pharmacy services, [2][3][4][5][6][7][8][9][10] no single measure takes the current breadth of services into consideration. Moreover, no single measure provides a mechanism for benchmarking the quality of pharmacy services nationwide.…”
mentioning
confidence: 99%
“…The PPDG is a ten-item measure that enhances the understanding of pharmaceutical care delivery in pharmacy practice by assessing the general factor of directive guidance (13). In essence, on a Likert-type scale of 0-4, patients rate the level of perceived instruction and feedback and goal setting received from their pharmacist during the past 3 months.…”
Section: Methodsmentioning
confidence: 99%